Theba pisana (Müller, 1774) (Gastropoda, Helicidae) and other alien land molluscs species in Argentina - Rumi Macchi Zubiaurre, Alejandra (2010)
The presence and distribution in Argentina of the invasive snail species Theba pisana is presented on the basis of a survey carried out in 10 beach resorts along the Atlantic coast of Buenos Aires Province. Additionally, complementary information and complete revision of material of other exotic terrestrial gastropods housed in museum collections was carried out, reporting herein seven new species for Argentina (Otala punctata, Hawaiia minuscula, Paralaoma servilis, Opeas goodalli, Vallonia pulchella, Vertigo ovata and Pupisoma dioscoricola), one for Colombia (Subulina octona), and two for Peru (S. octona and P. dioscoricola). At present, 42 introduced species of terrestrial gastropods have been recorded in nine countries of South America (Argentina, Bolivia, Brazil, Chile, Colombia, Paraguay, Peru, Uruguay and Venezuela). The most likely pathways for introduction of terrestrial gastropods, at least in Argentina, are horticultural development and urban and suburban transformation of original natural habitats.